Online Assessment amidst COVID-19 Pandemic: Exploring EFL Lecturers’ Practices and Perception - J, Syilvia Wenny (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Assessment is a part of everyday life in education, and it takes many forms for many different aims and levels. Measuring the students' progress, competency, and accountability was necessary during the learning process. This study aims to learn about lecturers' opinions and practices about using online assessment during Covid-19 in the context of ELT classrooms. The research method used is qualitative research with a case study approach. It was conducted in the Economics and Business Faculty of the University of Muhammadiyah Jambi. Participatory observation and interviews are used to acquire data. It found some crucial points; online media used by lecturers to assess students and the positive and negative sides of lecturers' online assessment practices. They choose online text messages like Whats App Group and Telegram Group for interactive assessment. For neat task submission, they chose Google Classroom. And for assessing speaking, Tiktok, Instagram and Youtube became alternative platforms. There are benefits and drawbacks that lecturers have encountered, such as effectiveness and efficiency in correcting students' tasks as its benefits, plagiarism, student cheating, and extending submission tasks as its drawbacks.